The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/2175-7860201869440
|View full text |Cite
|
Sign up to set email alerts
|

Comparative wood anatomy of Ficus cestrifolia (Moraceae) in two distinct soil conditions

Abstract: Wood anatomical traits respond to environmental variables and among them, soil has a direct impact on secondary xylem. This study compares the wood anatomy of two populations of Ficus cestrifolia occurring in two lowland formations of Southern Brazil (MAQ and SJS) with similar climate but different soil conditions. Wood samples were collected at breast height and prepared according to standard wood anatomy techniques. Soil samples were collected and subjected to a nutrient analysis. Wood was described quali an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…For example, Lens et al (2004) analyzed ecological trends in tropical forests and described the importance of the amount of precipitation in influencing the continuous traits of wood. Melo Júnior et al (2018) analyzed species under different climate and soil types and found differences in xylem structure favoring safety and water conduction efficiency, showing how hydraulic processes can influence plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Lens et al (2004) analyzed ecological trends in tropical forests and described the importance of the amount of precipitation in influencing the continuous traits of wood. Melo Júnior et al (2018) analyzed species under different climate and soil types and found differences in xylem structure favoring safety and water conduction efficiency, showing how hydraulic processes can influence plants.…”
Section: Discussionmentioning
confidence: 99%
“…They both also had higher vessel frequencies and smaller vessel diameters, shorter vessel lengths, lower vulnerability indices, and greater thickness of fibre-tracheids, which together represent a strategy that provides greater safety in water conduction. These differences in anatomical wood traits can be attributed to the structural adjustments of individuals in the different areas (Lens et al 2004;Melo Júnior et al 2018;Costa et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Within the tree, vessel frequency showed a different value in both sites; the highest value is in the branch part in Pacitan with 21.9 ± 9.4/mm 2 and in the root part in Klaten with 32.7 ± 19.6/mm 2 , while the lowest value was in the root part in Pacitan with 15.9 ± 2.0/mm 2 and in the stem part in Klaten with 18.3 ± 2.4/mm 2 . The higher value of vessel frequency in Klaten might be caused by the high availability of soil macro as well as a micronutrient and the organic matter content in the soil, as studied by Melo Junior et al (2018). This phenomenon is supported by Lima et al (2010) research, which showed that the increase in soil fertilizer dosage leads to a rise in the vessel frequency.…”
Section: Vesselsmentioning
confidence: 92%
“…Fibers with thicker walls (47%) were detected in eutrophic soil trees compared with oligotrophic soil. According to De Melo, Amorim, and Soffiatti [15], fertile soils affect the carbon allocation and, consequently, influence wood structure. The same authors also observed fibers with thicker walls in the xylem of Ficus cestrifolia growing in more fertile soil.…”
Section: Wood Anatomy In Response To Soil Typementioning
confidence: 99%
“…Soil fertility has induced xylem tissue modifications [6,10], including the size and arrangement of xylem cells. Such modifications have consequences for the efficiency and security of hydraulic transport in woody plants [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%